(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
According to theory of relativity matter space that interacts with each other. As it is explained matter tells the space how to bend space tells the matter how to move. But the question arises that how these interact. There exists a particle whose speed when at arrest is equal to the speed of light. Let call this particle A Space Particle in short we can call this Space Particle Sp. These Sp’s are everywhere in the space. When space matter interact with each other and matter changes the density of these space particles. Density of these particles decreases near the matter increases as we move away from the matter.